Deterministic Approach For Design Flood Estimation:Theory And Practice - Perpustakaan UGM, i-lib ([Yogyakarta] : Fak. Kedokteran UGM, 1996)
, Design flood estimation with certain average recurrence interval (ARI) is a first step in designing hydraulic structures. Inaccuracies in design floods may have a great effect, not only from an economic point of view, but also for human life. The determination of the design flood with a reliable results is not an easy task. Due to the difficulties in exaggerating the complex process of hydrology phenomena, deterministic approach is commonly used for design flood. The deterministic approach, however, should not be used for design flood estimation since there are several uncertainties inherent in this approach and the assumption commonly used, that the rainfall with certain ARI will produce a flood with the same ARI is not valid